Antibiotic prescriptions in the case management of acute watery diarrhea in under fives - Udoh, Ekong E.; Meremikwu, Martin M. (International Journal of Contemporary Pediatrics, 2017)
Background: Diarrhea disease is a leading cause of under-five mortality globally. The World Health Organization recommends low osmolality oral rehydration solution, zinc supplementation and adequate nutrition in the management. Antibiotic is indicated only in specific circumstances. This study was aimed at determining the antibiotic prescription in the management of under-fives with acute watery diarrhea. Methods: An audit of under-fives managed for acute watery diarrhea was conducted between January and February 2012. A multi-stage stratified random sampling technique was used to select 32 health facilities (21 primary and 11 secondary) from two local government areas of Cross River State. Case records of children managed for the condition six months prior to the audit were retrieved and evaluated. The appropriateness, types and frequency of antibiotic prescriptions were assessed. Results: A total of 370 case records were evaluated. Antibiotic was not indicated in any of the children but was prescribed for 291 (78.6%). Of this number, 169 (45.7%) received one antibiotic while 122 (33.0%) received two or more antibiotics. The difference in the prescription of multiple antibiotics between health workers in the primary and secondary facilities was statistically significant (p value = 0.00001). Metronidazole was the most prescribed antibiotic 228 (50.9%), followed by co-trimoxazole 88 (19.6%) and gentamicin 55 (11.8%). Conclusions: There is a high level of irrational antibiotic prescriptions in the State with oral metronidazole being the most prescribed. Periodic training of health workers on indications for antibiotic prescriptions in the management of diarrhea in under-fives is necessary.